2001
DOI: 10.1646/0006-3606(2001)033[0670:dbotfb]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Benefits of Twilight Foraging by the Insectivorous Bat Hipposideros speoris1

Abstract: Although bats are nocturnal, many species emerge from roosts to forage during twilight, despite a presumed high risk of predation at this time. Here, we describe twilight foraging by a maternity colony of Schneider's leafnosed bat (Hipposideros speoris) in the dry zone of Sri Lanka and determine the dietary benefits of such behavior. Bats usually began foraging during dusk, sometimes before sunset, and also foraged during twilight in the morning. Mean use of available twilight by four radio-tagged bats was 75 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…Although bats are nocturnal, many species emerge from roosts to forage during twilight. Field research on foraging by a maternity colony of Schneider's leafnosed bats (Hipposideros speoris) in Sri Lanka suggested that bats captured large numbers of insects that were only available or had marked peaks in abundance during twilight (Pavey et al 2001).…”
Section: Temporal Partitioning Between Predators and Preymentioning
confidence: 99%
“…Although bats are nocturnal, many species emerge from roosts to forage during twilight. Field research on foraging by a maternity colony of Schneider's leafnosed bats (Hipposideros speoris) in Sri Lanka suggested that bats captured large numbers of insects that were only available or had marked peaks in abundance during twilight (Pavey et al 2001).…”
Section: Temporal Partitioning Between Predators and Preymentioning
confidence: 99%
“…Though bats of various sizes (small to large) have been observed consuming mosquitoes [7,8] and mosquitoes have been identified in the stomach contents of bats [9,10] as well as in bat feces [8,11,12], many dietary studies have found mosquitoes to represent only a small proportion of bat diet, with other groups (e.g., moths and beetles) more common in bat diets [13]. However, the importance of mosquitoes and other small, soft-bodied prey may be understated due to the greater susceptibility of soft-bodied prey to the processes involved in mastication and digestion [14,15] and the bias associated with techniques available to study bat diet [14,16] .…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have also documented the linkage between insect and bat abundance (Rautenbach et al, 1996;Pavey et al, 2001), as insects constitute the principal food component of insectivorous bats (Williams and Singh, 1951;Holyoak, 2001). Furthermore, food preference, availability, and accessibility of prey (Kusch et al, 2004;Almenar et al, 2012) could have resulted in the differences in agroecosystems' ability to support insectivorous bats.…”
Section: Discussionmentioning
confidence: 99%
“…Nearly all insectfeeding bats are nocturnal (Speakman, 1995), occupy a diversity of habitat types, and exploit a wide variety of prey (Altringham, 1996;Kalko et al, 1996). Some authors have suggested that insect prey abundance influences the local occurrence of insectivorous bats (Rautenbach et al, 1996;Pavey et al, 2001). In other words, changes in the activity level of insects may influence the foraging behavior and activity levels of the bats.…”
Section: Introductionmentioning
confidence: 99%